Numerical Simulation: Fluctuation in Background Synaptic Activity Regulates Synaptic Plasticity - Takeda, Yuto; Hata, Katsuhiko; Yamazaki, Tokio; Kaneko, Masaki; Yokoi, Osamu; Tsai, Chengta; Umemura, Kazuo; Nikuni, Tetsuro (Frontiers in Systems Neuroscience, 2021)
Synaptic plasticity is vital for learning and memory in the brain. It consists of long-term potentiation (LTP) and long-term depression (LTD). Spike frequency is one of the major components of synaptic plasticity in the brain, a noisy environment. Recently, we mathematically analyzed the frequency-dependent synaptic plasticity (FDP) in vivo and found that LTP is more likely to occur with an increase in the frequency of background synaptic activity. Meanwhile, previous studies suggest statistical fluctuation in the amplitude of background synaptic activity. Little is understood, however, about its contribution to synaptic plasticity. To address this issue, we performed numerical simulations of a calcium-based synapse model. Then, we found attenuation of the tendency to become LTD due to an increase in the fluctuation of background synaptic activity, leading to an enhancement of synaptic weight. Our result suggests that the fluctuation affects synaptic plasticity in the brain.